Automatic chili seeds remover for household and small-medium enterprises as an alternative of hand cutting method - Siti Maryam, Sharun; Muhammad Firdaus, Abdul Halim Yap; Nur Haizal, Mat Yaakob@Ariffin; Sharifah Hanis Yasmin, Sayid Abdullah (2021)
Chili is the main ingredient and one of the spices that is widely used to improve flavor in the meal. Spicy meals provided with dried chili make some people feel spicy yet delicious and they become more desirable to be eaten. Naturally, chili contains a large number of seeds and it became more challenging to separate the seeds from the chili. It takes longer time and a lot of manpower to prepare dried chili paste manually. Hence to reduce meal preparation time, some people opted for the use of instant chili paste in their cooking. However, the chili paste contains additional preservatives to ensure longer shelf life. This situation is unfavorable for the consumer's health. On the other hand, the existing chili seed remover is large and expensive and only suitable for the large food industry application. The purpose of this study is to design and develop a beta prototype of an automatic dried chili seed remover machine (ADCSRM) which is ergonomic and portable and can be tested with different weights of dried chili per operation. It is also can help the small industry and the housewife to optimize their works. ADCSRM is designed to cut dried chili and remove the seeds by using specifically designed blade. This machine has seven main parts and used a blender motor with adjustable speed function. The result of this study showed that the ADCSRM machine can separate a minumum of 50 g up to 250 g of dried chili per operation. The maximum time for each operation is around 40-45 s depending on the weight of dried chili input. The machine was invented in a small size with a simple mechanism and easy to use. In conclusion, by using ADCSRM it can reduce the meal preparation time, number of labor as well as the cost of chili paste preparation.